Frugivory by the black-eared opossum Didelphis aurita in the Atlantic Forest of southern Brazil: Roles of sex, season and sympatric species - Nilton C. Cáceres; Lucineia Z. Prates; Ivo R. Ghizoni-Junior; Maurício E. Graipel (Biotemas)
Our objective in this study was to examine the frugivory performed by the black-eared opossum, Didelphis aurita Wied-Neuwied, 1826, in an area of the coastal Atlantic Forest of southern Brazil, including differences between sexes, seasonal variation, and relationships to other sympatric marsupials. We collected 63 fecal samples from a trap grid over a six-month period and analyzed seed presence, seed number and richness,  and diversity of fruit species in feces. Diversity of fruit items was estimated by the Shannon index. Results showed a high variability in fruit consumption along the seasons, but no sexual difference in consumption. Sympatric marsupial species, including D. aurita, showed substantial differences in frugivory which may be related to body size, space use and differences in the foraging behavior of such species.